SYMBOLIC MEANING IN REBA TRADITIONAL RITUALS IN THE NGADA ETHNIC COMMUNITY OF EAST NUSA TENGGARA (CULTURAL COMMUNICATION STUDY) - Daniella Renatta Mogyi; RR Roosita Cindrakasih (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
The Reba Traditional Ritual is a tradition of the Ngada people in East Nusa Tenggara. This ritual is performed as a way to honor ancestors, express gratitude, and pray for safety and a better life. This study aims to identify the symbols present in the Reba Traditional Ritual, understand the meanings of these symbols, and examine how cultural communication occurs within the ritual. In this study, the researcher employed a descriptive qualitative method. Data were collected through observation, in-depth interviews, and documentation with informants consisting of traditional leaders, religious leaders, and the younger generation of the Ngada community. The results of the study indicate that the symbols in the Reba Traditional Ritual consist of object symbols, action symbols, and verbal symbols. These symbols convey meanings of gratitude, respect for ancestors, togetherness, well-being, hard work, self-purification, and hope for a better life. Furthermore, the Reba Traditional Ritual also serves as a medium of cultural communication that conveys social, spiritual, and cultural values to future generations. These findings align with the Theory of Cultural Communication developed by Samovar and Richard, which explains that culture is transmitted through the process of communication.